PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP DI KECAMATAN LAMBOYA KABUPATEN SUMBA BARAT - Agustinus Woda Laka; Andrian Wira Syahputra; Fenetson Pairikas; Ezra Tari (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
The work discipline of teachers could be seen in adherence to rules, school governance, and universal social values. Work motivation as a driving factor that encourages a teacher to carry out their duties  professionally and responsibly. The combination of these two variables will have a positive impact on performance.The problem of this research is formulated as follow: (1) To what extent does work discipline affect teacher performance? (2) To what extent does work motivation influence teacher performance? (3) To what extent both work discipline and work motivation influence teacher performance? This research  involved 99 teachers in 7 schools in Lamboya District, West Sumba Regency as the sample. Data collection techniques consist of questionnaires and documentation, analyzed by multiple regression and analysis of effective and relative contributions. the work discipline variable, work motivation simultaneously influences teacher performance. the calculated F test value of 58.518 with the sig parameter 0.05 seemed to be a linear pattern. The multiple regression equation is known: Y = 11.171 + 0.186X1 + 1.062X2. The total effective contribution both work discipline and work motivation is 54.9%.